Greylag Geese Anser anser depart earlier in spring: an analysis of goose migration from western France over the years 1980-2005 - Fouquet, Michel H.; Schricke, Vincent; Fouque, Carol (Wildfowl, 2013)
France is located on the Atlantic flyway of the Northwest European Greylag Goose Anser anser population, between its Nordic breeding grounds (Sweden and Norway) and its southernmost wintering sites in Spain. Large numbers of geese pass over France during autumn and spring, particularly in west-central France which is on the birds’ main migration route to Spain. Analysis of the phenology of spring migration over 26 years (1980–2005) in west-central France showed that spring migration occurs between January and mid-April, with the main movements occurring between the end of January and mid-March, peaking in mid-February. The date on which the first migratory flights were observed each year, and also the median migration dates, both demonstrated an increasingly early start of the migration period over the 26-year period. Whereas in the 1980s migration began at the beginning of February, now the first birds are seen as early as mid January. This is consistent with studies of neck-banded birds re-sighted along the flyway, which found that the geese have been arriving earlier on the breeding grounds. The temporal changes in spring migration in France may be attributable to one or a combination of factors, such as changes in wintering conditions in Spain, a succession of mild winters along the flyway, climate change permitting an early onset of the breeding season in the Nordic areas and, perhaps, a higher proportion of birds wintering further north in the Netherlands.